The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1024/2674-0052/a000032
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of sleep deprivation in ultra-endurance cycling

Abstract: Abstract. Introduction: The popularity of ultra-endurance cycling is increasing. Amongst race participants, sleep deprivation and periods of intermittent or acutely short sleep are common. Scientific research has typically focussed on the physiological or competitive performance based impact of these sleep-related paradigms. However, there is limited evidence about the mental health effects of sleep patterns in ultra-endurance cycling, despite established links between sleep deprivation and psychiatric and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Equally, suicide risk is not discussed in the literature, though personal accounts from UEAs who have psychiatric disorders note that depression and suicidal ideation are intertwined with training for long distance events [ 60 , 61 ]. The associations between extreme sleep patterns in-competition and mental health disorders after the race are also missing from extant literature in our review, but these onset possibilities have been identified in other contexts [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equally, suicide risk is not discussed in the literature, though personal accounts from UEAs who have psychiatric disorders note that depression and suicidal ideation are intertwined with training for long distance events [ 60 , 61 ]. The associations between extreme sleep patterns in-competition and mental health disorders after the race are also missing from extant literature in our review, but these onset possibilities have been identified in other contexts [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Latella et al's simulated Grand Tour demonstrated how substantial physical demands intra-race may induce adverse implications for mood, vigour, and sleep amount and quality [41]. In ultraendurance cycling events, where sleep deprivation can be a prominent phenomenon, it has been suggested that this can potentially entail short-and long-term psychological difficulties [55]. Additionally, whilst they did not estimate prevalence rates, Liebrenz et al hypothesise that ADHD may likely be pharmacotherapeutically undertreated in elite-level riders, due to mental health and doping stigma [42].…”
Section: Other Mental Health Conditionsmentioning
confidence: 99%
“…The physical challenges of RAAM are well-documented in general media and academic research; for example, nutrition and hydration needs are of critical importance for successful race completion [5], particularly given RAAM's high-altitude environments [12]. However, concurrently, RAAM's stringent intra-race demands raise concerns for athlete mental health, especially in relation to sleep deprivation [10]. Ultra-endurance competitions are largely underexamined in sports psychiatry literature [11], yet phenomenological insights from RAAM reveal inherent risk factors.…”
Section: Athlete Wellbeing In the Race Across Americamentioning
confidence: 99%
“…Likewise, there could be other obstacles given RAAM’s sociocultural reputation [34] and the wider persistence of mental health stigma within sporting contexts [37]. To that end, alongside community engagement, detailed scholarly research into the mental health effects of ultra-endurance cycling races is needed to inform relevant appropriate regulatory schemes, especially since findings remain limited within sports psychiatry [10, 11].…”
Section: Regulatory Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation